Minimum Price for Sales of Shofiya Products in Beteng Trade Center Solo in the Perspective of Law Number 5 1999 on the Prohibition of Monopoly Practices and Unfair Business Competition - Adinda Zahira Fortuna; M. Usman (Jurnal Al-Hakim: Jurnal Ilmiah Mahasiswa, Studi Syariah, Hukum dan Filantropi, 2023)
This study aims to determine the review of Law No. 5 of 1999 related to the determination of the minimum price for sales of Shofiya products in Beteng Trade Center Solo. This research was motivated by the determination of the minimum sales price (HMP) of Shofiya products in Beteng Trade Center Solo, where price determination included a form of agreement prohibited in Law No. 5 of 1999 concerning the Prohibition of Monopoly Practices and Unfair Business Competition. The primary data used in this study came from Shofiya managers and Shofiya resellers.  The results of this study show that in the determination of HMP Shofiya products in Beteng Trade Center Solo there is no element of agreement between Shofiya and the reseller.  In addition, there is no evidence that the determination of HMP causes market competition to be disrupted. Thus, it can be concluded that the determination of HMP for Shofiya products does not violate Law Number 5 of 1999 concerning the Prohibition of Monopoly Practices and Unfair Business Competition.